2022
DOI: 10.1002/nag.3332
|View full text |Cite
|
Sign up to set email alerts
|

FEM×DEM multi‐scale model for cemented granular materials: Inter‐ and intra‐granular cracking induced strain localisation

Abstract: In this paper, we present a multi‐scale model that combines the finite element method (FEM) and the discrete element method (DEM) to study the behaviour of cemented granular materials (CGM) at both the sample (macroscopic) and particle (microscopic) scales, taking into account inter‐ and intra‐granular cracking. At the microscopic scale, the material is made up of Volume Elements (VE) composed of particles. Their mechanical behaviour is modelled by the DEM. In the VEs, we find circular grains (single particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 94 publications
0
6
0
3
Order By: Relevance
“…The motion of particles is obtained by solving the equation of second Newton's law with a time discretization and a third order predictor‐corrector scheme 41 . It should be noted that considering a more complicated grain–grain interaction law is straightforward and already implemented in our multi‐scale FEM×DEM model, as recently demonstrated in Nguyen et al 26 …”
Section: Fem×dem With Local Second Gradient Enhancement: a Brief Desc...mentioning
confidence: 94%
See 2 more Smart Citations
“…The motion of particles is obtained by solving the equation of second Newton's law with a time discretization and a third order predictor‐corrector scheme 41 . It should be noted that considering a more complicated grain–grain interaction law is straightforward and already implemented in our multi‐scale FEM×DEM model, as recently demonstrated in Nguyen et al 26 …”
Section: Fem×dem With Local Second Gradient Enhancement: a Brief Desc...mentioning
confidence: 94%
“…This coupling method provides a cross-scale tool and has given rise to several publications. [26][27][28][29][30][31] In this way, the DEM-based constitutive model can be considered as a traditional constitutive law with thousands of state variables, represented by grain coordinates and geometry, contact list, contact orientation, interaction forces, etc. However, it was observed that the mesh dependency was also encountered in FEM×DEM calculation when strain localization occurred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the complex mesostructure of clay rocks, one possibility to evaluate their impacts on mesoscale and macroscale overall mechanical responses is to use a multi‐scale approach. Such approach allows to study a statistically equivalent Representative Elementary Volume (REV for 3D case) or Representative Elementary Area (REA for 2D case) to determine the behaviour of the equivalent homogeneous medium 24–33 . In particular, computational homogenisation methods, 34–36 also known as multi‐scale analyses, have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Such approach allows to study a statistically equivalent Representative Elementary Volume (REV for 3D case) or Representative Elementary Area (REA for 2D case) to determine the behaviour of the equivalent homogeneous medium. [24][25][26][27][28][29][30][31][32][33] In particular, computational homogenisation methods, [34][35][36] also known as multi-scale analyses, have emerged. They include, among others, finite element squared (FE 2 ) 24,[37][38][39][40] and FEM-DEM 41 methods for continuous media at the large scale and heterogeneous/discrete material at the small scale.…”
Section: Introductionmentioning
confidence: 99%